Dysregulated gastric microbial communities and functional shifts in chronic atrophic versus non-atrophic gastritis: a Helicobacter pylori-Negative observational study - Hong Yao; Tingting Liu; Yiming Chen; Ling She; Tingfeng Wu; Dongsong Liu; Yuhong Deng; Yubin Han; Kai Chen; Jianmin Deng; Jue Zhang; Jinfeng Chen; et al. (BMC Gastroenterology)
Abstract Background Helicobacter pylori (H. pylori) infection was identified as a substantial risk factor for gastric cancer development, but the eradication of H. pylori did not necessarily lead to a reduction in the incidence of gastric cancer. Non-Helicobacter pylori (non-H. pylori) bacteria in the stomach are involved in the transformation of gastritis carcinoma. The aim of this study was to characterize the microbiome composition of the gastric mucosa and its functions in non-H. pylori (H. pylori-negative) patients with chronic atrophic gastritis (CAG) and chronic non-atrophic gastritis (CNAG). Methods Fourteen CNAG samples and twenty-three CAG samples were collected. The composition of the gastric microbiome was analyzed using 16 S rDNA gene sequencing. The bioinformatic analysis was performed using alpha and beta diversity analyses, PICRUSt2, and linear discriminant analysis effect size (LEfSe). Results The two groups shared the same most abundant bacterial phyla (Pseudomonadota, Bacillota, Actinomycetota, and Bacteroidota). The top 5 most abundant bacterial genera in the CAG group were Sphingomonas, Ralstonia, Brevundimonas, Methyloversatilis, and Pseudomonas. In the CNAG group, the top genera were Brevundimonas, Ralstonia, Sphingomonas, Methyloversatilis, and Acinetobacter. Differential analysis revealed distinct genera between groups: the CAG group showed enrichment in Sphingomonas, Ralstonia, Bradyrhizobium, Roseateles, and Acidithiobacillus, while the CNAG group was enriched in Brevundimonas, Rhodococcus, Hydrogenophaga, Bacteroides, and Leifsonia (p < 0.05). Sphingomonas exhibited a positive correlation with Acidithiobacillus but negative correlations with Brevundimonas, Hydrogenophaga, and Leifsonia. Pathways related to xenobiotic biodegradation, metabolism, signal transduction, cofactor/vitamin metabolism, cancer, infectious diseases, and digestive system were enriched in the CAG group. In contrast, the CNAG group showed enrichment in amino acid metabolism, translation, replication/repair, and terpenoid/polyketide metabolism. Conclusion Gastric mucosal microbiota dysbiosis and functional shifts are significantly associated with chronic atrophic gastritis. Taxa such as Sphingomonas and Ralstonia, enriched in CAG patients, may indicate microbial signatures associated with early atrophic transition and provide candidates for further mechanistic validation.